The Role of Tax Literacy in The 12% Vat Rate and Lifestyle on Purchasing Decisions - Enggar Nursasi; Siti Munfaqiroh (PT. Maju Malaqbi Makkarana, 2026)
This study examines the effects of the VAT rate increase and lifestyle on purchasing decisions among consumers in the Malang area, with tax literacy as a moderating variable. An explanatory quantitative design was applied using PLS-SEM (SmartPLS 4.0) with 81 respondents selected through purposive sampling. The results indicate that VAT rate increase (β = 0.537; p = 0.000) and lifestyle (β = 0.285; p = 0.024) each have a significant positive effect on purchasing decisions. Tax literacy does not directly affect purchasing decisions (β = 0.066; p = 0.465), but functions as a significant moderator: it strengthens the effect of the VAT rate increase (β = 0.309; p = 0.037) while weakening the effect of lifestyle (β = −0.337; p = 0.031). These findings suggest that tax literacy may shift the basis of consumer decision-making toward a more rational-fiscal orientation, offering preliminary evidence for the value of tax education programs that address everyday consumption contexts